I believe that the mean is 6
Use the website Symbolab. It's helped with all of my calculus problems.
The answers D, the explanation is that it’s basically common sense just look for the same numbers and make it make sense :)
Answer:
0.01
Step-by-step explanation:
Answer:
1. x = 2
2. x = 61/25
Step-by-step explanation:
Solve for x:
5 (x - 2) - 3 (2 - x) = 0
-3 (2 - x) = 3 x - 6:
3 x - 6 + 5 (x - 2) = 0
5 (x - 2) = 5 x - 10:
5 x - 10 + 3 x - 6 = 0
Grouping like terms, 5 x + 3 x - 10 - 6 = (3 x + 5 x) + (-6 - 10):
(3 x + 5 x) + (-6 - 10) = 0
3 x + 5 x = 8 x:
8 x + (-6 - 10) = 0
-6 - 10 = -16:
8 x + -16 = 0
Add 16 to both sides:
8 x + (16 - 16) = 16
16 - 16 = 0:
8 x = 16
Divide both sides of 8 x = 16 by 8:
(8 x)/8 = 16/8
8/8 = 1:
x = 16/8
The gcd of 16 and 8 is 8, so 16/8 = (8×2)/(8×1) = 8/8×2 = 2:
Answer: x = 2
_____________________________
Solve for x:
Solve for x:
3 (2 x - 7) + (7 x + 2)/3 = 0
Put each term in 3 (2 x - 7) + (7 x + 2)/3 over the common denominator 3: 3 (2 x - 7) + (7 x + 2)/3 = (9 (2 x - 7))/3 + (7 x + 2)/3:
(9 (2 x - 7))/3 + (7 x + 2)/3 = 0
(9 (2 x - 7))/3 + (7 x + 2)/3 = (9 (2 x - 7) + (7 x + 2))/3:
(9 (2 x - 7) + 2 + 7 x)/3 = 0
9 (2 x - 7) = 18 x - 63:
(18 x - 63 + 7 x + 2)/3 = 0
Grouping like terms, 18 x + 7 x - 63 + 2 = (18 x + 7 x) + (2 - 63):
((18 x + 7 x) + (2 - 63))/3 = 0
18 x + 7 x = 25 x:
(25 x + (2 - 63))/3 = 0
2 - 63 = -61:
(25 x + -61)/3 = 0
Multiply both sides of (25 x - 61)/3 = 0 by 3:
(3 (25 x - 61))/3 = 3×0
(3 (25 x - 61))/3 = 3/3×(25 x - 61) = 25 x - 61:
25 x - 61 = 3×0
0×3 = 0:
25 x - 61 = 0
Add 61 to both sides:
25 x + (61 - 61) = 61
61 - 61 = 0:
25 x = 61
Divide both sides of 25 x = 61 by 25:
(25 x)/25 = 61/25
25/25 = 1:
Answer: x = 61/25